Hemostatic powder application for control of acute upper gastrointestinal bleeding in patients with gastric malignancy - Kim, Yeong Jin; Park, Jun Chul; Kim, Eun Hye; Shin, Sung Kwan; Lee, Sang Kil; Lee, Young Chan (Endoscopy International Open, 2018)
Background and study aims Despite use of various endoscopic therapies in patients with tumor-related bleeding, various rates of successful immediate hemostasis and short-term rebleeding have been reported. We aimed to evaluate preliminary results of use of the EndoClot polysaccharide hemostatic system (PHS) in patients with acute upper gastrointestinal bleeding (UGIB) from a gastric malignancy.Patients and methods We retrospectively analyzed data from a prospectively collected database of 12 patients with acute UGIB from a gastric malignancy who had been treated with EndoClot PHS. The EndoClot air compressor was used to propel 2 g of absorbable modified polymer particles onto the bleeding site. We checked successful immediate hemostasis, rebleeding events and mortality within 30 days. Results Twelve patients were enrolled in the study. The median patient age was 72.5 years (range, 57 – 89). The initial median hemoglobin level was 6.75 g/dL (range, 5.4 – 8.9). The median systolic blood pressure was 114 mmHg (range, 86 – 153). Eleven patients had advanced gastric cancer and one patient had a gastrointestinal stromal tumor. The lower body of the stomach was the most common tumor location (58.3 %), and the median tumor size was 40 mm (range, 15 – 100). Immediate hemostasis was achieved in all patients, and rebleeding developed in 2 of 12 patients (16 %), 3 and 5 days after treatment. There were no significant Endoclot PHS-related adverse events, and there was no all-cause mortality at 30 days after the intervention.Conclusions Endoclot PHS represents a new alternative, complementary, and promising therapy for patients with an acute UGIB from a gastric malignancy.